2018
DOI: 10.1080/17461391.2018.1486460
|View full text |Cite
|
Sign up to set email alerts
|

Key determinants of time to 5 m in different ventral swimming start techniques

Abstract: The aim of this study was to determine the biomechanical parameters that explain ventral start performance in swimming. For this purpose, 13 elite swimmers performed different variants of the ventral start technique. Two-dimensional video analyses of the aerial and underwater phases were used to assess 16 kinematic parameters from the starting signal to 5 m, and an instrumented starting block was used to assess kinetic data. A Lasso regression was used to reduce the number of parameters, providing the main det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
6
32
1
Order By: Relevance
“…The importance of the flight distance was consistent with Peterson Silveira et al [ 8 ], who reported a strong relationship (r ≈ −0.895) between the flight distance in front and rear kick starts and the 5 m time. The peak velocity investigated in the present study was the peak head velocity and not the center of mass velocity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The importance of the flight distance was consistent with Peterson Silveira et al [ 8 ], who reported a strong relationship (r ≈ −0.895) between the flight distance in front and rear kick starts and the 5 m time. The peak velocity investigated in the present study was the peak head velocity and not the center of mass velocity.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has identified factors contributing to the time spent in these segments, e.g., start (block position, reaction/block time, push-off, flight, entry and underwater) [ 6 , 7 , 8 , 9 ], turn (5 m approach, pivot time, push-off, underwater distance and velocity) [ 10 , 11 , 12 ], clean swimming velocity (cycle length and cycle rate) [ 13 , 14 ], and the finish (timing of the wall touch and the trajectory of the hands) [ 15 ]. Therefore, the winner of a race or the swimmer with the fastest finishing time is not always the swimmer with the highest mean clean swimming velocity, but rather the swimmer who performs well on all of the race segments [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although useful insights into relevant performance determining variables may be obtained in this manner, these distances, and the associated times, do not correspond to the aforementioned start phases. Since swimmers enter the water well before crossing the 5-m line [ 20 , 21 ], the time required to do so is also dependent on the characteristics of the underwater phase [ 22 ], and the same holds for the 7.5-m and 10-m line. As a result, using this approach, it is difficult to gain a clear understanding of how the actions in one phase affect the actions in the next, and how the overall start performance results from the performance in each phase.…”
Section: Introductionmentioning
confidence: 99%
“…There are also strong empirical grounds for adopting a focus on entry state to better understand the dive start. Previous research has identified several kinematic variables pertaining to the swimmer’s state at water entry that are associated with dive start performance, including the swimmer’s distance from the block [ 10 , 20 , 21 , 27 ], the horizontal velocity of the swimmer’s centre of mass [ 9 , 10 , 24 ], and the swimmer’s angle with the water surface [ 21 ]. That these variables contribute to start performance can be readily understood from basic mechanical considerations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation